Desenvolvimento de um compósito de espuma rígida de poliuretana de mamona e fibras de sisal para isolação térmica - Neira, Dorivalda Santos Medeiros (2011)
The search for sustainable technologies that can contribute to reduce energy consumption is a great challenge in the field of insulation materials. In this context, composites manufactured from vegetal sources are an alternative technology. The principal objectives of this work are the development and characterization of a composite composed by the rigid polyurethane foam derived from castor oil (commercially available as RESPAN D40) and sisal fibers. The manufacture of the composite was done with expansion controlled inside a closed mold. The sisal fibers where used in the form of needlepunched nonwoven with a mean density of 1150 g/m2 and 1350 g/m2. The composite characterization was performed through the following tests: thermal conductivity, thermal behavior, thermo gravimetric analysis (TG/DTG), mechanical strength in compression and flexural, apparent density, water absorption in percentile, and the samples morphology was analyzed in a MEV. The density and humidity percentage of the sisal fiber were also determined. The thermal conductivity of the composites was higher than the pure polyurethane foam, the addition of nonwoven sisal fibers will become in a higher level of compact foam, reducing empty spaces (cells) of polyurethane, inducing an increase in k value. The apparent density of the composites was higher than pure polyurethane foam. In the results of water absorption tests, was seen a higher absorption percent of the composites, what is related to the presence of sisal fibers which are hygroscopic. From TG/DTG results, with the addition of sisal fibers reduced the strength to thermal degradation of the composites, a higher loss of mass was observed in the temperature band between 200 and 340 °C, related to urethane bonds decomposition and cellulose degradation and its derivatives. About mechanical behavior in compression and flexural, composites presented a better mechanical behavior than the rigid polyurethane foam. An increase in the amount of sisal fibers induces a higher rigidity of the composites. At the thermal behavior tests, the composites were more mechanically and thermally resistant than some materials commonly used for thermal insulation, they present the same or better results. The density of nonwoven sisal fiber had influence over the insulation grade; this means that, an increaser in sisal fiber density helped to retain the heat